Personal, clinical and social characteristics of inpatients with long hospital stay in the acute wards of the Hospital Víctor Larco Herrera - Abanto, Roger (2018)
Objective: To identify the general characteristics that influence a long hospital stay in the acute wards of a mental health institution and to compare them with the reason for admission. Materials and methods: A descriptive, retrospective and cross-sectional study was conducted at the Hospital Víctor Larco Herrera in patients between 18 and 65 years of age staying longer than 60 days in the acute wards. Medical records review, data collection in structured files, and statistical analysis through IBM SPSS Statistics Base 22.0 were performed. Main outcome measures were the frequencies, mean and p value (obtained by chi square test) in the variables of personal, clinical and social characteristics. Results: Out of the total number of inpatients, 52 % were staying longer than 60 days, 45 % were youths and young adults (median = 35.89, SD = 10.45), 60 % were women, 61 % had secondary education, 81 % were single, 74 % were unemployed, 74 % were admitted through the emergency department, 55 % were readmitted, 53 % were from Lima, 62 % had schizophrenia which was the most frequent diagnosis, 61 % showed comorbidities, 64 % presented an aggressive behavior on admission, 63 % showed a stable progression, 47 % were admitted due to legal reasons, 47 % were admitted due to clinical reasons, 74.2 % mainly received combination therapies, 52 % did not experience social or family abandonment, 66 % were accompanied by their relatives, 71.4 % were accompanied by the police, 72.6 % had a dysfunctional family, 51.6 % were supported by their parents, and 92 % were covered by the Comprehensive Health Service (SIS). There is greater statistical significance in gender, marital status, origin, admission route, patient type or condition (new or readmitted), and company of relatives and other persons at admission. Conclusions: Hospital stay is affected by personal factors such as gender and marital status in patients admitted due to legal reasons. The origin, clinical factors such as the admission route and condition, and social factors such as the company of relatives and other persons, have influence on patients admitted due to clinical reasons.